Differential fault attack on FeW - Min XIE; Jiaqi LI; Feng TIAN (Tongxin xuebao)
In order to evaluate the security of the lightweight block cipher FeW,a differential fault attack method was proposed and discussed using a single byte random fault model.In this method,a single byte random fault was introduced on the right side of the last round of FeW to recover the key based on the statistical characteristics of S-box difference distribution,and the difference information was obtained using the characteristics of the linear diffusion function.The experiment results show that the complete key recovery can be achieved with an average of 47.73 and 79.55 fault injections for FeW-64-80 and FeW-64-128 respectively.If 210exhaustive calculations are added to the key recovery process,the number of average fault injections required can be reduced to 24.90 and 41.50.This attack is effective on FeW.